Non‐orthogonal frequency division multiplexing based on sparse representation. Issue 16 (10th September 2018) - Fu, Xiaomei; Chen, Li; Yang, Jingyu
Abstract : This study proposes a sparse non‐orthogonal frequency division multiplexing (S‐NOFDM) based on sparse representation to improve the spectral efficiency of orthogonal frequency division multiplexing (OFDM). The subcarriers of S‐NOFDM are generated from a subset of OFDM orthogonal subcarriers, which therefore requires less spectral resource. Each selected OFDM subcarrier is shifted into a group of overlapping subcarriers with different time delays. The modulated signal is produced by solving the sparse representation of the input signal under the generated set of subcarriers. The demodulation is simply a linear combination of generated subcarriers with the recovered modulated signal. Simulation results show that the proposed S‐NOFDM can achieve better bit error rate performance in an additive white Gaussian noise channel and a little worse than OFDM in a Rayleigh channel, with less frequency resources required.